Literature Review : Factors Affecting Birth Weight and its Management - Indrawati, Nuke Devi; Dewi, Maria Ulfah Kurnia; Mustika, Dian Nintyasari; Puspitaningrum, Dewi (P3M Universitas 'Aisyiyah Surakarta, 2024)
The literature review has the aim of reviewing and comparing the similarities of several research results regarding the factors that influence the occurrence of low birth weight babies and their management methods in several hospitals in Indonesia. Literature review method with this study was carried out by conducting a literature review by searching several national journals. Literature search using several keywords, namely